Publishing Manifestos : an international anthology from artists and writers - Pichler, Michalis (Cambridge Massachusetts London : The MIT press Massachusetts Institute of Technology,., 2022)
AND Publishing, Oswald de Andrade, Archive Books, Art-Rite, Rasheed Araeen, Tauba Auerbach, Michael Baers, Bibi Bakare-Yusuf, Ricardo Basbaum, Derek Beaulieu, Bernadette Corporation, Riccardo Boglione, Bombay Underground, Jorge Luis Borges, bpNichol, Kate Briggs, Broken Dimanche Press, Eleanor Vonne Brown, Urvashi Butalia, Ulises Carrión, Mariana Castillo Deball, Paul Chan, Chimurenga, Arpita Das, Anita Di Bianco, Guy Debord, Constant Dullaart, Craig Dworkin, Ntone Edjabe, Zenon Fajfer, Marina Fokidis, General Idea, Annette Gilbert, Girls Like Us, Gloria Glitzer, Marianne Groulez, Alex Hamburger, Karl Holmqvist, Lisa Holzer, Mahmood Jamal, Tom Jennings, Ray Johnson, David Jourdan, Sharon Kivland, Kione Kochi, Kwani?, Bruce LaBruce, Tan Lin, El Lissitzky, Alessandro Ludovico, Sara MacKillop, Steve McCaffery, Jonathan Monk, Simon Morris, Mosireen, León Munoz Santini, Takashi Murakami, Deke Nihilson, Aurélie Noury, Johnny Noxzema, Clive Phillpot, Michalis Pichler, Seth Price, Riot Grrrl, Carlos Soto Román, Allen Ruppersberg, Joachim Schmid, Oliver Sieber, Paul Soulellis, Matthew Stadler, Gertrude Stein, Paul Stephens, Hito Steyerl, Mladen Stilinović, Katja Stuke, Temporary Services, Nick Thurston, TIQQUN, Elisabeth Tonnard, V. Vale, Eric Watier, Erik van der Weijde, Lawrence Weiner, Eva Weinmayr, Jan Wenzel, Stephen Willats, Gil J Wolman, zubaan
boek